2015
DOI: 10.1021/acs.jpcc.5b05541
|View full text |Cite
|
Sign up to set email alerts
|

Ex Situ and in Situ Surface Plasmon Monitoring of Temperature-Dependent Structural Evolution in Galvanic Replacement Reactions at a Single-Particle Level

Abstract: The galvanic replacement reaction has recently been established as a standard protocol to create complex hollow structures with various compositions and morphologies. In the present study, the structural evolution of Ag nanocubes with Au precursors is monitored at the single-particle level by means of ex situ and in situ characterization tools. We explore two important features distinct from previous observations. First, the peak maximum of localized surface plasmon resonance (LSPR) spectra abruptly shifts at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
(82 reference statements)
3
15
0
Order By: Relevance
“…In the past, we have shown (as subsequently confirmed by others) that the behavior observed in single-nanoparticle trajectories is a result of a two-step mechanism: There is a precursor step in the galvanic transformation of the nanoparticle, which involves the stochastic nucleation of a void (collection of Ag vacancies) on the surface of the Ag nanoparticle. The waiting time signifies the period before a void larger than a critical size is nucleated in the nanoparticle. Following the formation of a critical void in a nanoparticle, rapid galvanic exchange takes place across the bulk of the nanoparticle, limited only by the mass transport of depositing Au 3+ ions and/or dissolving Ag + ions.…”
Section: Methodssupporting
confidence: 57%
“…In the past, we have shown (as subsequently confirmed by others) that the behavior observed in single-nanoparticle trajectories is a result of a two-step mechanism: There is a precursor step in the galvanic transformation of the nanoparticle, which involves the stochastic nucleation of a void (collection of Ag vacancies) on the surface of the Ag nanoparticle. The waiting time signifies the period before a void larger than a critical size is nucleated in the nanoparticle. Following the formation of a critical void in a nanoparticle, rapid galvanic exchange takes place across the bulk of the nanoparticle, limited only by the mass transport of depositing Au 3+ ions and/or dissolving Ag + ions.…”
Section: Methodssupporting
confidence: 57%
“…Noble metal (gold and silver) nanoparticles have proven to be an effective route to increase the light-harvesting capability in solar cells due to their localized surface plasmon resonance effects (LSPR). By adjusting the shape and size of the metal nanoparticles, the characteristic wavelength of the plasmon effect can be changed [28][29][30], thereby improving light absorption, carrier generation, and power conversion efficiency; this has been successfully used to improve the PCEs of solar cells [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…14 Apart from the morphology, the composition of nanoparticles also inuences their catalytic property. Various AgAu bimetallic hollow nanostructures such as nanosphere, 15,16 nanocubes, [17][18][19] nanowires, 20 nanorods, 14 nanotubes, 21 nanoshells, 22 nanobowls, 23 and nanoframes 24 are highly efficient in various catalytic reactions such as the reduction of nitrophenol, 14 degradation of methylene blue, 25 aniline oxidation, 24 and oxidation of various organic molecules. 26 Zheng et al compared Au nano boxes with their hollow counterpart "nanocages" and reported them as catalytically more active.…”
Section: Introductionmentioning
confidence: 99%